2019
DOI: 10.3390/f11010035
|View full text |Cite
|
Sign up to set email alerts
|

Foliar and Wood Traits Covary along a Vertical Gradient within the Crown of Long-Lived Light-Demanding Species of the Congo Basin Semi-Deciduous Forest

Abstract: Plant functional traits have shown to be relevant predictors of forest functional responses to climate change. However, the trait-based approach to study plant performances and ecological strategies has mostly been focused on trait comparisons at the interspecific and intraspecific levels. In this study, we analyzed traits variation and association at the individual level. We measured wood and leaf traits at different height locations within the crown of five individuals of Pericopsis elata (Harms) Meeuwen (Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…Overall, our results strongly support the pledge for the inclusion of trait information below the species scale, when associating traits with ecosystem functions (Albert et al 2010;Messier, McGill, and Lechowicz 2010;Siefert et al 2015;Hulshof and Swenson 2010;Kafuti et al 2020). In particular, we could demonstrate for multiple traits the great share of intraindividual trait variation, which has not been found in such a consistent way and in a comparable extent so far.…”
Section: Effects Of Interacting Soil Nutrient Availability and Divers...supporting
confidence: 80%
See 1 more Smart Citation
“…Overall, our results strongly support the pledge for the inclusion of trait information below the species scale, when associating traits with ecosystem functions (Albert et al 2010;Messier, McGill, and Lechowicz 2010;Siefert et al 2015;Hulshof and Swenson 2010;Kafuti et al 2020). In particular, we could demonstrate for multiple traits the great share of intraindividual trait variation, which has not been found in such a consistent way and in a comparable extent so far.…”
Section: Effects Of Interacting Soil Nutrient Availability and Divers...supporting
confidence: 80%
“…In addition to substantial variation within species, traits can also vary greatly within an individual (i.e., intra-individual variation). So far, in plant functional ecology, only few studies have zoomed in from intra-specific trait variation to intra-individual trait variation (Umaña et al 2018; Messier, McGill, and Lechowicz 2010; Auger and Shipley 2013; Kang et al 2014), and several have suggested that intra-individual trait variation can even be greater than between-individuals trait variation (Herrera, Medrano, and Bazaga 2015; Kafuti et al 2020). Ignoring the intra-individual scale of variation means neglecting an essential aspect of the answer to understanding the structure and functioning of plant communities.…”
Section: Introductionmentioning
confidence: 99%
“…In a closed forest, significant micro-environmental gradients occur across the canopy ( Parker, 1995 ). For instance, one important factor that determines trait variation is the position (i.e., the height) within an individual plant, because in forests as height increases water availability is increasingly limited ( Kafuti et al., 2020 ). In savannas, however, species are usually short and in an open canopy; thus, variation in leaf functional traits within the canopy are predicted to be much lower than that in closed forests with taller trees.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in tropical rain forests, Parashorea chinensis H. Wang, a dominant species, has been observed to shift adaptive strategies throughout development from shade-tolerant to competitive in response to changes in both light and tree height level ( Deng et al., 2020 ). At the top of the canopy, twigs of some tree species respond to restricted water-supply and potential water deficits by producing many vessels with minimal size, which reduces the possibility that the entire conduction system will collapse due to embolisms in single vessels ( Kafuti et al., 2020 ). However, previous studies have been limited by small sample sizes due to the difficulties of accessing the upper parts of trees in forest canopies ( Keenan and Niinemets, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This endemic and endangered timber species has a disjunctive natural distribution area ranging from Ivory Coast to the Democratic Republic of the Congo (DRC). Easily recognized by its creamy or greyish flaky bark, its compound leaves, and its fruits, the species can reach 60 m height with a diameter at breast height (DBH) up to 160 cm (Kafuti et al, 2020). The species has a high tolerance of soil moisture content and reaches it optimum on rich phosphorus and sulphur clay soils (Bourland et al, 2012).…”
Section: Study Species and Sitesmentioning
confidence: 99%